Association Between Alcohol Consumption and Risk of Bladder Cancer: A Dose-Response Meta-Analysis of Prospective Cohort Studies - Lao, Yongfeng; Li, Xiaolong; He, Lijuan; Guan, Xin; Li, Rongxin; Wang, Yanan; Li, Yanyou; Wang, Yunchang; Li, Xu; Liu, Shuai; Dong, Zhilong (Frontiers in Oncology, 2021)
Abstract Background Controversial results of the association between alcohol consumption and risk of bladder cancer were reported by the previous meta-analyses. Objective To quantitatively investigate the association between alcohol consumption and risk of bladder cancer based on prospective cohort studies, and explore whether there is potential dose-response relation. Method PubMed, EMBASE, the Cochrane Library databases, China Biology Medicine disc (CBM), and Chinese National Knowledge Infrastructure (CNKI) were searched for relevant studies. Categorical meta-analysis was performed for risk estimates of any alcohol consumers versus non-drinkers as well as different drinking degrees (light, moderate, and heavy) versus none. And two-stage generalized least-squares regression and restricted cubic spline, as well as fixed-effects dose-response models, were used for linear and nonlinear dose-response relation exploration. Results 9 prospective cohort studies including 1,971,396 individuals were finally included. We did not observe a significant association between alcohol intake and the risk of bladder cancer in the entire population. Linear association was detected in those who consumed alcohol from liquor or spirits (P linear=0.02). One drink increment each day of alcohol could elevate the risk of bladder cancer by 9% (RR=1.09; 95%CI: 1.01-1.17). Alcohol was a risk factor of bladder cancer for male drinkers (RR=1.23; 95%CI: 1.13-1.35; I2=3.7%), while none linear or nonlinear relation was found. Conclusion No significant association between alcohol consumption and bladder cancer risk was found in the entire population, but there was a linear dose-response relation in those who consume alcohol from liquor or spirits. Alcohol may elevate the risk of bladder cancer in males in a dose-independent way.